(untitled) (Global Journal of Human-Social Science, 2024)
Promoting the mastery of language skills is one of the determining factors for the success of the integration process in the United Europe which also determines its policy in the educational space Learning a foreign language means not only effective communication between citizens of different countries but also getting to know the culture of the community to which they belong Along with the creation of a favorable language environment among EU member states attitudes of respect understanding and acceptance of others and their diversity are formed The article presents a theoretical study based on an in-depth study of literary and Internet sources on the linguistic situation linguistic minorities and foreign language education in some countries belonging to the European Union The main emphasis is on analyzes related to the organization of training the status of the languages studied and the evaluation of the obtained results